Exchange rate volatility and non-oil exports in Nigeria : An empirical investigation / Sa’ad Babatunde Akanbi...[et al.] - Akanbi, Sa’ad Babatunde; Yusuf, Hammed Agboola; Oluwaseyi, Musibau Hammed (Faculty of Business and Management, Universiti Teknologi MARA, Puncak Alam Campus, 2017)
The adoption of a flexible exchange rate system since 1986 in Nigeria has made the country witnessed varying rate of the naira vis-à-vis the U.S dollar. This paper examines exchange rate volatility with ARCH model and its various extensions (GARCH, TGARCH, and EGARCH) using quarterly exchange rate series from 1986-Q1 to 2014-Q4.The impact of exchange rate volatility on non-oil exports was also examined using Error Correction Model (ECM) with two different measures of volatility. The results obtained confirm the existence of exchange rate volatility and also found a significant negative effect on non-oil export performance in Nigeria. Therefore, the Nigerian government should ensure an appropriate policy mix that not only ensures a stable and realistic exchange rate but also conducive atmosphere for production and exportation.